Alkali‐Metal‐Intercalated Percolation Network Regulates Self‐Assembled Electronic Aromatic Molecules. Issue 11 (24th January 2019) - Hu, Yong; Zhong, Guohua; Guan, Ying‐Shi; Lee, Nam Hoon; Zhang, Yuan; Li, Yang; Mitchell, Travis; Armstrong, Jason N.; Benedict, Jason; Hla, Saw‐Wai; Ren, Shenqiang
Abstract: In the continuously growing field of correlated electronic molecular crystals, there is significant interest in addressing alkali‐metal‐intercalated aromatic hydrocarbons, in which the possibility of high‐temperature superconductivity emerges. However, searching for superconducting aromatic molecular crystals remains elusive due to their small shielding fraction volume. To exploit this potential, a design principle for percolation networks of technologically important film geometry is indispensable. Here the effect of potassium‐intercalation is shown on the percolation network in self‐assembled aromatic molecular crystals. It is demonstrated that one‐dimensional (1D) dipole pairs, induced by dipole interaction, regulate the conductivity, as well as the electronic and optical transitions, in alkali‐metal‐intercalated molecular electronic crystals. A solid‐solution growth methodology of aromatic molecular films with a broad range of stability is developed to uncover electronic and optical transitions of technological importance. The light‐induced electron interactions enhance the charge‐carrier itinerancy, leading to a switchable metal‐to‐insulator transition. This discovery opens a route for the development of aromatic molecular electronic solids and long‐term modulation of electronic efficacy in nanotechnologically important thin films. Abstract : Metallic evidence that intercalation‐induced one‐dimensional conducting channels regulate the conductivity, electronic, and optical transition is found in alkali‐metal‐intercalated p‐terphenyl. These findings may have implications in the basic mechanism for the regulation of superconducting phase development and long‐term modulation of electronic efficacy in nanotechnologically important thin film geometry.